CNS Complications of Mycoplasma Pneumoniae - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Three cases of acute central nervous system disease occurring subsequent to infection with M pneumoniae are reported from University College, Institute of Child Health, and Great Ormond Street Hospital, London, UK.